ALIH KODE DAN CAMPUR KODE PENUTUR BAHASA JAWA DALAM PENGGUNAAN BAHASA INDONESIA SISWA KELAS VIII SMP NEGERI 5 SATU ATAP KECAMATAN WASILE KABUPATEN HALMAHERA TIMUR - Iin Setyowati; Huby Saufan Hilmi (Jurnal Bilingual, 2021)
Purpose this research to Describe the from of shift code and mixed code speaker Java language in the use of Indonesia language for class VIII students of  SMP Land 5 one roof subdistrict Wasile the Halmahera East, Identifies the cause of the shift code and mixed code speaker Java language in the use of Indonesia language for class VIII students of  SMP Land 5 one roof subdistrict Wasile the Halmahera East. This research descriptive qualitative method. Used data is the data primary and data secondary. The source of the data is 26 students that in the area language Java. Technique collection of used data is observations, the interview, and the rocording. Technique see (supervision), technique capable (interview). Technique analyses data used the descripsive qualitative (data reduction, exposure to data , and conclusion drawing and verification). Be based on data analyzing, obtained conclud that shift code and mixed code speaker Java language in the use of Indonesia language for class VIII students of SMP Land 5 one roof subdistrict Wasile the Halmahera East thare are 3 form of, is; (a) Shift code in the from of the word, phrase, and clause, (b) Mixed code in the from of the word, phrase, and clause. Shift code happened namely is from Indonesia language to deep Java language or reverse. Mixed code happened namely is mixed code in the Java language. The cause of the shift code speaker Java language in the use of Indonesia language for class VIII students of SMP Land 5 one roof subdistrict Wasile the Halmahera East that is; (1) Natural, (2)  Influenced other people/opponents talk, (3) More comfortable Java language, (4) Not to familiarize yourself use the Indonesia lenguage a good and right, (5) A friend in the area Java language, (6) Changing the topic of conversation. The cause of the mixed code speaker Java language in the use of Indonesia language for class VIII students of SMP Land 5 one roof subdistrict Wasile the Halmahera East that is; (1) Natural, (2) Influenced other people/opponents talk, (3) More comfortable Java language, (4) Not to familiarize yourself use the Indonesia lenguage a good and right, (5) Another friend can’t speak Indonesia , (6) A friend in the area Java language.